2008
DOI: 10.1177/1403494808095086
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fiscal implications of subsidizing in-vitro fertilization in Sweden: A lifetime tax perspective

Abstract: Based on results presented here we conclude that State-funded IVF in Sweden does not negatively impact the long run fiscal budget. Conversely, over an average lifetime an IVF offspring returns a positive net value to the State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
3
8
0
2
Order By: Relevance
“…According to the results, the child’s initial IVF investment represented a 700% net return in discounted US dollars. In another modified GA model, which was developed for Sweden,33 it was revealed that state-funded IVF does not negatively impact the long-run fiscal budget; conversely, over an average lifetime, an IVF offspring returns a positive net value to the state. Another model, developed for Brazil, estimated that the fiscal contribution generated by each IVF-conceived citizen can justify an initial government investment in infertility treatment, but this initial expenditure may be compensated for by the fiscal contribution in the next generation 34.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, the child’s initial IVF investment represented a 700% net return in discounted US dollars. In another modified GA model, which was developed for Sweden,33 it was revealed that state-funded IVF does not negatively impact the long-run fiscal budget; conversely, over an average lifetime, an IVF offspring returns a positive net value to the state. Another model, developed for Brazil, estimated that the fiscal contribution generated by each IVF-conceived citizen can justify an initial government investment in infertility treatment, but this initial expenditure may be compensated for by the fiscal contribution in the next generation 34.…”
Section: Discussionmentioning
confidence: 99%
“…All costs In the model have been converted from Danish Krones (DKK) to Euros (€) based on an exchange rate of €1 = 7.45 DKK. Broadly speaking there are four major life stages considered in the model: early child, education, working and retirement (Svensson et al, 2008).…”
Section: Modelling Frameworkmentioning
confidence: 99%
“…The cost-efficiency of state investments in IVF is assessed by calculation of net income, usually expressed through taxes and other state revenues received from the working population. Economic evaluations revealed that there were net tax benefits of IVF financing in both high-income countries (eg, the USA, UK, Denmark, Sweden)37 and medium-income countries like Brazil 8. Net income gained from the IVF populations in all countries studied was positive; however, the largest gain was found for the UK (£109,939), while the smallest gain was found for Brazil (US$ 61,428).…”
Section: Introductionmentioning
confidence: 93%